A Psicologia Da Arquitetura Segundo Heinrich Wölfflin: Contexto E Tradução - Santos, Diana Oliveira Dos [UNIFESP] (2017)
The task talks about the characterization studies of the structure of Wölfflin‟s thought, his studies in the Germany of the XIX century and the context right after his degree, emphasizing the aspects and dialogue with German philosophy, the development of the experimental psy-chology during the period and his relationship with Jacob Burckhardt and some of the main theorists of the period. For this, the work is concluded with the main object of the present work, the translation of Psicologia della Architettura from the italian to the portuguese (Pro-legômenos para uma Psicologia da Arquitetura), base of the study where the author talks about constructive elements and sensorial, physical and psychological aspects that affect the observer, together or individually. The text helps to understand the root of his formation, pre-senting concepts that persisted in his works beyond those that the author suggests to be devel-oped.